Pengembangan Usaha Produk Pangan Olahan Berbasis Kacang Koro Pedang Menuju Komersialisasi di Desa Tahai Baru Kabupaten Pulang Pisau: Business Development of Processed Food Products Based on Jack Bean Towards Commercialization in Tahai Baru Village, Pulang Pisau - Kusumadati, Wijantri; Zubaidah, Siti; Ichriani, Gusti Irya; Chotimah, Hastin Ernawati Nur Chusnul (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The partner of the service activity is the Joint Business Group (KUBE) of Tahai Baru Village, Maliku District, Pulang Pisau, which produces processed food with the raw material of jack bean. The problems faced by partners include the resulting Jack bean tempeh products that pungent smell and are easily destroyed; the packaging of Jack bean tempeh chips, which is still very simple and without labels; and limited marketing. The purpose of this service activity is to improve the quality of processed food products of jack bean through standardization of product processing, developing the selling value of products through packaging, labeling, and product legality, so that it is commercially viable. The implementation methods used include counseling, training, and mentoring. The result of this activity is a "Tahai Baru" brand jack bean tempeh chip product, using updated product processing methods so that it does not taste and pungent smell, with six (6) flavor variants, packaged in aluminum foil standing pouch packaging, attractive label design, and by the law, and has a Business License Number (NIB) Number: 9120019231896.